Hukum dan Etika Bisnis pada Akuntansi, Ekonomi, Keuangan Perusahaan dan Investasi - Dewi, Putri Purnama; Purba, Dea Natalia (Asosiasi Dosen Akuntansi Indonesia, 2025)
This research discusses the role of law and business ethics in accounting, economics, corporate finance, and investment. In the modern business world, decision-making is not only based on economic and financial factors, but must also consider applicable legal regulations and ethical principles. Business law provides guidelines regarding contracts, consumer protection, and intellectual property rights, while business ethics emphasizes transparency, social responsibility, and fair business practices. Using a qualitative case study method in the manufacturing industry, this research finds that compliance with law and business ethics increases financial transparency, prevents unhealthy business practices, and supports company sustainability. Therefore, the integration of law and ethics in business management is a key factor in creating a competitive and sustainable business environment.